Testing the Level of Social Desirability During Job Interview on White-Collar Profession - Preiss, Marek; Mejzlíková, Tereza; Rudá, Adéla; Krámský, David; Pitáková, Jindra (Frontiers in Psychology, 2015)
Social desirability as a tendency to present oneself in a better light rather than in a truthful manner is common feature presented during job interviews. Previous studies mainly focused on blue-collar professions and therefore authors researched contrary set of white-collar professions in three sub-studies with four different participant groups (legal professions; police officers; controls and university students influenced by scenarios; overall N=636). It was hypothesized that candidates for legal profession would show similar tendency towards social desirability, when compared with controls. Furthermore, police officers were hypothesized to show similar levels of social desirability as legal professions. Lastly, participants in the instruction manipulation condition were hypothesized to show increased levels of social desirability in tender situation as compared to the honest situation. All groups were tested with Balanced Inventory of Desirable Responding (BIDR, Paulhus, 1984). Statistical analyses revealed statistically significant differences for both subscales of BIDR when comparing legal professions and control group. Similarly, increased levels of social desirability were detected in police officer candidates as well as in university students in the tender situation compared with students in the honest situation. The overall results indicated that it is typical for white-collar candidates to adapt to the testing situation and it cannot be expected to see different behavior from legal profession candidates as was originally expected.